Effect of variety and nutrient on insect pest infestation of Amaranthus spp - ABO Ogedegbe; AE Ezeh (Journal of Applied Sciences and Environmental Management)
Amaranthus species is one of the plants often considered as the most important green leaf vegetable in Nigeria and other countries. Its production has been plagued with an array of factors including incidence of insect pest. This experiment took place in Agricultural farm of University of Benin, Edo state Nigeria from February to April 2013 and 2014. The aim was to investigate the effect of Nutrient and Variety on Insect Pest infestation of Amaranthus spp. The experimental design used was completely randomized design with three replicates comprising a factorial combination of three types of Soil and three varieties of Amaranth. The result showed that Amaranthus cruentus suffered more insect pest attack than other Amaranthus used and that Amaranths planted on poultry manure attracted more insect pests than Amaranths planted on other Nutrients. These results can be employed as part of cultural control methods in the management of insect pests of Amaranths.